THE PARENTS’ ROLE OF ENGLISH LEARNING ACHIEVEMENT: STUDENTS’ AND TEACHERS’VOICES A CASE STUDY AT SD N 1 SENDANGMULYO SLUKE REMBANG - Selly Devinda Dewi; Rahmawati Sukmaningrum; Wiyaka Wiyaka (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2026)
This study investigates parental roles in supporting students' English learning achievement in a remote primary school setting. Using a descriptive qualitative approach, data were collected from twenty fifth-grade students and an English teacher at SD N 1 Sendangmulyo through questionnaires, semi-structured interviews, and academic documentation. The data were analyzed using the interactive model of condensation, display, and conclusion drawing. The results reveal that parental roles primarily manifest as emotional motivators and digital facilitators, providing smartphones and internet access to compensate for geographical barriers. While significant linguistic barriers limit direct academic tutoring, parents act as strategic coordinators by utilizing "social capital," such as more proficient siblings. These findings underscore the importance of emotional anchoring and technological mediation in enhancing language outcomes in rural EFL contexts. This study provides practical insights for educators to synchronize home-school communication in underserved regions.